2014
DOI: 10.1002/pits.21798
|View full text |Cite
|
Sign up to set email alerts
|

Child‐centered Play Therapy in the Schools: Review and Meta‐analysis

Abstract: The authors conducted a meta-analysis and systematic review that examined 23 studies evaluating the effectiveness of child centered play therapy (CCPT) conducted in elementary schools. Meta-analysis results were explored using a random effects model for mean difference and mean gain effect size estimates. Results revealed statistically significant effects for outcome constructs, including externalizing problems (d = 0.34), internalizing problems (d = 0.21), total problems (d = 0.34), self-efficacy (d = 0.29), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 44 publications
7
133
1
4
Order By: Relevance
“…CCPT is identified as the most popular theoretical approach to play therapy (Lambert et al, 2005). Additionally, metaanalyses have reported positive and meaningful effects for children who participate in CCPT (Bratton, Ray, Rhine & Jones, 2005;Lin & Bratton, 2015;Ray, Armstrong, Balkin & Jayne, 2015).…”
Section: Person-centered Approach To Anxietymentioning
confidence: 98%
“…CCPT is identified as the most popular theoretical approach to play therapy (Lambert et al, 2005). Additionally, metaanalyses have reported positive and meaningful effects for children who participate in CCPT (Bratton, Ray, Rhine & Jones, 2005;Lin & Bratton, 2015;Ray, Armstrong, Balkin & Jayne, 2015).…”
Section: Person-centered Approach To Anxietymentioning
confidence: 98%
“…Specifically, Ray, Armstrong, Balkin, and Jayne (2015) reviewed studies addressing child centered play therapy in elementary schools and found it to be an efficacious treatment for internalizing problems, externalizing problems, total problems, self-efficacy, academic, and other concerns. Results from the above four meta-analyses provided evidence in support child centered play therapy with school-aged children.…”
Section: Play Therapy and Internalizing And Externalizing Behaviorsmentioning
confidence: 99%
“…This effort has concluded in recognition of CCPT as an evidence‐based intervention by mental health organizations and agencies. In the last 20 years, randomized controlled trials have resulted in statistically and practically significant outcomes in favor of the effectiveness of CCPT (Lin & Bratton, 2015; Ray, Armstrong, Balkin, & Jayne, 2015). However, this focus on meeting positivistic standards is a source of discussion among CCPT therapists; specifically, there is the concern regarding movement toward manualization of an approach that is inherently focused on meeting and responding to the individual child in a flexible and spontaneous manner.…”
Section: Where Are We Going?mentioning
confidence: 99%